2023
DOI: 10.3390/antiox12071384
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Frański, R.; Beszterda-Buszczak, M. Comment on “Villalva et al. Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori. Antioxidants 2022, 11, 1849”

Abstract: Franski and Beszterda-Buszczak [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The Villalva’s data have been criticized by Franski and Beszterda-Buszczak [ 21 ]. Although they do not question the quality of the paper, these authors raised questions about the correctness of some compounds identified by Villalva et al However, Villalva clarified all the doubts of Franski and Beszterda-Buszczak in a reply paper [ 22 ].…”
mentioning
confidence: 99%
“…The Villalva’s data have been criticized by Franski and Beszterda-Buszczak [ 21 ]. Although they do not question the quality of the paper, these authors raised questions about the correctness of some compounds identified by Villalva et al However, Villalva clarified all the doubts of Franski and Beszterda-Buszczak in a reply paper [ 22 ].…”
mentioning
confidence: 99%